∫ 7 1 7 ( x 3 − 2 9 x 2 + 2 8 1 x − 8 9 0 ) d x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x 3 − 2 9 x 2 + 2 8 1 x − 8 9 0 = ( x − 1 0 ) 3 + ( x − 1 0 ) 2 + ( x − 1 0 ) \ Now sub u = x − 1 0 and we integrate from -7 to 7 So cubic and linear vanish becomes 3 ( x − 1 0 ) 3 from -7 to 7 3 6 8 6
This was if lower bound was 3...
Problem Loading...
Note Loading...
Set Loading...
I = ∫ 7 1 7 ( x 3 − 2 9 x 2 + 2 8 1 x − 8 9 0 ) d x = ∫ 7 1 7 ( x 3 − 2 1 x 2 + 1 4 7 x + 3 4 3 − 8 x 2 + 1 3 4 x − 5 4 7 ) d x = ∫ 7 1 7 ( ( x − 7 ) 3 − 8 ( x 2 − 1 4 x + 4 9 ) + 2 2 x − 1 5 4 − 1 ) d x = ∫ 7 1 7 ( ( x − 7 ) 3 − 8 ( x − 7 ) 2 + 2 2 ( x − 7 ) − 1 ) d x = ∫ 0 1 0 ( u 3 − 8 u 2 + 2 2 u − 1 ) d u = 4 u 4 − 3 8 u 3 + 1 1 u − u ∣ ∣ ∣ ∣ 0 1 0 = 3 2 7 7 0 ≈ 9 2 3 . 3 3 3 Let u = x − 7